Concepts and methods for landscape multifunctionality and a unifying framework based on ecosystem services - Mastrangelo, Matías Enrique (2014)
The potential of landscapes to supply multiple benefits to society beyond commodities production has received increasing research and policy attention. Linking the concept of multifunctionality with the ecosystem services (ES) approach offers a promising avenue for producing scientific evidence to inform landscape planning, e.g., about the relative utility of land-sharing and land-sparing. However, the value for decision-making of ES-based multifunctionality assessments has been constrained by a significant conceptual and methodological dispersion. To contribute towards a cohesive framework for landscape multifunctionality, we analyse case studies of joint ES supply regarding ten criteria designed to ultimately answer four aspects: (i) the multifunctionality of what (e.g., landscapes), (ii) the type of multifunctionality (e.g., based on ES synergies), (iii) the procedure of multifunctionality assessments, and (iv) the purpose of multifunctionality. We constructed a typology of methodological approaches based on scores for criteria describing the evaluation method and the level of stakeholder participation in assessments of joint ES supply. Surveyed studies and underlying types of methodological approaches (spatial, socio-spatial, functional, spatio-functional) differed in most criteria. We illustrate the influence of methodological divergence on planning recommendations by comparing two studies employing contrasting approaches (spatial and functional) to assess the joint supply of wildlife habitat and agricultural production in the Argentine Chaco. We distinguish between a pattern-based and process-based multifunctionality, where the latter can only be detected through approaches considering the ecological processes (e.g., ES complementarities) supporting the supply of multiple ES (functional and spatio-functional). Finally, we propose an integrated approach for assessing a socially-relevant process-based multifunctionality.